Particle number analysis of lipoprotein subclasses by gel permeation HPLC in patients with cholesteryl ester transfer protein deficiency - Okada, Takeshi; Ohama, Tohru; Okazaki, Mitsuyo; Kanno, Kotaro; Matsuda, Hibiki; Sairyo, Masami; Zhu, Yinghong; Saga, Ayami; Kobayashi, Takuya; Masuda, Daisaku; Koseki, Masahiro; Nishida, Makoto; et al. (PloS one, 2018)
We previously reported that patients with cholesteryl ester transfer protein (CETP) deficiency (CETP-D) have a higher prevalence of atherosclerotic cardiovascular disease, in spite of increased HDL-C levels. However, characterization of HDL in CETP-D has not been well described. Therefore, we examined HDL particle number (PN) rather than HDL-C level. Nine patients with CETP-D and 9 normolipidemic subjects were enrolled. We performed gel permeation high-performance liquid chromatography (GP-HPLC) analysis, determined the cholesterol and triglyceride composition of all lipoprotein subclasses, and calculated the PN of each subclass, which consisted of 3 VLDL (large, medium, and small), 4 LDL (large, medium, small, and very small), and 5 HDL (very large, large, medium, small, and very small) subclasses. The PNs of large and medium LDL were significantly lower in CETP-D than that in healthy subjects (0.66- and 0.63-fold decrease, respectively; p<0.001), whereas the PN of very small LDL, which is known to be atherogenic, was significantly higher (1.36-fold increase, p = 0.016). The PNs of very large and large HDL in CETP-D were markedly higher than that in healthy subjects (19.9- and 4.5-fold increase, respectively; p<0.001), whereas the PNs of small and very small HDL, which have more potent anti-atherogenic functions, were significantly lower (0.76- and 0.61-fold decrease, respectively; p<0.001). We have assessed the PNs of detailed subclasses of patients with CETP-D for the first time. The PN of larger HDL was markedly increased, that of smaller HDL was decreased, and that of very small LDL was increased, suggesting that CETP-D has pro-atherogenic lipoprotein properties.